2001
DOI: 10.1046/j.0956-540x.2001.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific strong ground motion prediction using 2.5-D modelling

Abstract: Summary An algorithm was developed using the 2.5‐D elastodynamic wave equation, based on the displacement–stress relation. One of the most significant advantages of the 2.5‐D simulation is that the 3‐D radiation pattern can be generated using double‐couple point shear‐dislocation sources in the 2‐D numerical grid. A parsimonious staggered grid scheme was adopted instead of the standard staggered grid scheme, since this is the only scheme suitable for computing the dislocation. This new 2.5‐D numerical modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…An explosive source is of little relevance to earthquake related site effect studies since it cannot explain the observed radiation patterns and is dominated by compressional waves. The successful numerical implementation of a double-couple point source into the computational grid was presented by VIDALE and HELMBERGER (1987), GRAVES (1996), PITARKA (1999) and NARAYAN (2001). NARAYAN (2001) demonstrated that 3-D and 2.5-D radiation pattern, using a double-couple point source based on moment tensor source formulation, corroborates with each other in the xz-plane.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…An explosive source is of little relevance to earthquake related site effect studies since it cannot explain the observed radiation patterns and is dominated by compressional waves. The successful numerical implementation of a double-couple point source into the computational grid was presented by VIDALE and HELMBERGER (1987), GRAVES (1996), PITARKA (1999) and NARAYAN (2001). NARAYAN (2001) demonstrated that 3-D and 2.5-D radiation pattern, using a double-couple point source based on moment tensor source formulation, corroborates with each other in the xz-plane.…”
Section: Introductionmentioning
confidence: 72%
“…Moment tensor source formulation was used in implementing the source into the computational grid (PITARKA, 1999 andNARAYAN, 2001). The second derivative of convolution of a polynomial window ½f1 À ðs À 1Þ 2 g 3 and the Gaussian function ½expfÀsðt À t 0 Þ 2 g with a dominant period 't 0 ' was used as an excitation function.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 3 more Smart Citations